Harmonizing Kuranglabih Values in River-Based Traditional Trade: Lok Baintan Floating Market Study - Apriati, Yuli; Budimansyah, Dasim; Pasani, Chairil Faif; Nurdin, Encep Syarief (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
This study examines the integration of local wisdom, Islamic values, and early childhood engagement in the river-based traditional trade at the Lok Baintan Floating Market. The study delves into the enduring "Kuranglabih" principle rooted in the values of the Banjar community, which permeates traditional trade. This enduring principle, which harmonizes with traditional trade, undergoes examination through the qualitative case study approach. "Kuranglabih" denotes a term used in traditional trade at Lok Baintan Floating Market, describing a bargaining process centered on sincerity and generosity, devoid of causing harm to either the seller or the buyer. Data were collected through observation, interviews, and documentation to produce a comprehensive record of cultural phenomena. The research instruments utilized in this study underwent a validation process to ensure their reliability and effectiveness in collecting data.The results demonstrate that the 'Kuranglabih' value imbues trading with 'mabrur,' echoing Allah’s virtuous principles, and has a positive impact on trading while aligning with virtuous principles. Early childhood engagement serves as a foundation for value transmission and the sustainability of cultural continuity within Banjar society. This study underscores early childhood engagement’s role in value transmission, nurturing sustainable cultural continuity within Banjar society. The study highlights this intricate interplay’s multi-dimensional nature of harmonizing local wisdom, Islamic values, and early childhood engagement at the Lok Baintan Floating Market.